2015
DOI: 10.1089/gtmb.2014.0213
|View full text |Cite
|
Sign up to set email alerts
|

Association of a Methylene Tetrahydrofolate Reductase C677T Polymorphism with Several Blood Chemical Levels in a Chinese Population

Abstract: Our data demonstrate that the MTHFR C677T polymorphism is positively correlated with an increased risk of hypertension through an increase in HCY levels. The blood lipid correlative index was different between male and female hypertension patients and controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…Regarding lipid profiles, the MTHFR 677T allele is associated in non-obese patients with unfavourable serum lipid profiles in several studies (15, 18, 21, 24, 26, 28). In this study, we detected low levels of triglycerides and cholesterol in overweight/obese individuals carrying the TT genotype.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding lipid profiles, the MTHFR 677T allele is associated in non-obese patients with unfavourable serum lipid profiles in several studies (15, 18, 21, 24, 26, 28). In this study, we detected low levels of triglycerides and cholesterol in overweight/obese individuals carrying the TT genotype.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the 677T allele has been linked with overweight/obesity risk, dyslipidemias, and diabetes in several populations. However, so far, the studies have been controversial (4, 5, 7, 8, 9, 10, 11, 12, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30). Here, we analyzed whether there is an association of the MTHFR 677C>T polymorphism with overweight and obesity, as well as its relationship with lipid profile, glucose level, and anthropometric measurements in a young Mexican population.…”
Section: Introductionmentioning
confidence: 99%
“…Many previous studies have explored the relationship between the MTHFR C677T polymorphism and serum or plasma lipid profiles in humans, with some indicating that the T allele was associated with unfavourable lipid profiles [8–11, 17, 3639], whereas the others reported null association [40–43]. An interesting study by Zhang et al indicated that the MTHFR 677 T allele significantly increases the serum levels of TC and LDL-C in both Chinese Bai Ku Yao and Han populations [10].…”
Section: Discussionmentioning
confidence: 99%
“…MTHFR rs1801133 C/T genotype may be a risk factor of hypertension in a Caucasian population [ 44 ]. People carried MTHFR rs1801133 T allele enhanced the risk of hypertension among Chinese in Taiwan [ 45 ], Chinese Han population in Shihezi city, Xinjiang Province, China [ 46 ], Chinese from Jiangxi Province [ 47 ], and male Spaniard [ 48 ]. DBP and SBP levels of female hypertensive patients were different among the different genotypes of MTHFR in the Baiku Yao population in China [ 49 ].…”
Section: Discussionmentioning
confidence: 99%